Influence of social media on young adults' buying behaviour - Osman, Syuhaily; Shamsuddin, Nurul Fazlina (MACFEA, 2023)
This study aimed to identify social media's influence on buying behavior among young adult consumers. 200 young adults in Kuantan, Pahang, were selected through a simple random sampling method. Data were collected using a set of survey questionnaires and a five-point Likert scale to measure the independent variables (attitude, source of information, credibility, and interactivity) and dependent variable (consumer buying behavior). The results showed that young adults in Kuantan obtained high mean scores for social media buying behavior (mean = 3.87), attitude (mean = 3.91), source of information (mean = 3.87), credibility (mean = 3.86) and interactivity (mean = 3.86). Besides that, Pearson correlation analysis showed that attitude (r = 0.946, p = .000), source of information (r = 0.970, p = .000), credibility (r = 0.980, p = .000), and interactivity (r = 0.973, p = .000) were significantly and positively associated with buying behavior through social media. Furthermore, the results of multiple linear regression showed that the three predictors could explain as much as 94.7 of the variation in respondents’ social media buying behavior, with the source of information as the most significant predictor (Beta = 0.721; p = 0.001). The study concluded that social media had been found to influence consumer purchasing behavior significantly. Therefore, consumers should be able to use social media as best as possible to make their purchasing decisions wisely and carefully. There may even be misleading advertisements based solely on testimonials. Marketers or businesses should also ensure that the products they advertise are accompanied by clear product information and endorsed by a clean image opinion leader to meet the needs of consumers.